UUM Assets Tracking System (UATS) - Alhroot, Hussein Abdalhaleem Hussein (2008)
Assets Tracking System include those applications that user encounter directly or indirectly in Assets Management. The problem is Tracking Assets will consume a lot of time, effort, and a huge number of staff, the probability of mistakes during data entry, and in generating report for the assets may also occur. This study proposes a requirement model of "UUM Assets Tracking System " as a solution for the problem faced by the Staff in UUM. The system for managing Assets in UUM Campus was tested with a prototype and found to be working.